[Des]construção e [res]significação dos direitos humanos: um estudo com vivências de ensino-aprendizagem e análises sociológicas - Brito, Gabrielle Amâncio Bertolli Venâncio (2024)
Faced upon a convoluted moment over a polarized political context with different and opposite ideas, the conception of human rights lies as “privilege” for criminals. Such annalysis is sustained by both population and commom sense. This work presents the results of a research made with second grade classes from Ensino Médio (Brazilian High school) in a full-time public school in Goiânia, Goiás. In order to do so the following investigation problem has been set: How to (de)construct the human rights conception and (re)define it through sociology classes? This research aims to understand the human rights concept lying (or not) in Ensino Médio students’ speech, opposing the bias that such rights are “bandits” privilege. To deconstruct such alignaments – sustained by social and historical visions shaped within neoliberalism interest, means to construct a critical perspective of human rights biased over multiculturalism through a teaching Project that sustains this Dissertation process. The pedagogic interventions were set upon the teaching Project entitled “Afinal, o que são esses tais direitos humanos?” (Afterall what are the so-called human rights?) developed in Sociology classes. Such Project is a founding part of the previously mentioned research and also part of the Professional Master in Science stricto sensu from the post-grad program in Basic Education teaching in the Research and Teaching Education Applied center (CEPAE – Centro de Ensino e Pesquisa aplicada à Educação) from the Federal University of Goiás (UFG), thus named educational product, available in appendix. The research is made upon qualitative bias and fundamented over theoreticals that worked with the history of human rights and its concepting, such as Giuseppe Tosi (2004), Norberto Bobbio (2004), Hannah Arendt (1989, João Dornelles (2013) and Boaventura Santos (1997). The theoretical fouding is set also in human rights educators such as Candal (2008), Sacavino (2013) and Paulo Freire (2019), scholars that annalysed a democratic and humanizing education. Such authors work with the plurality of understandings in the concept of human rights in several theoretical and historical perspectives, developed over a democratic focus, universally centralizer of rights, or with a neoliberalism perspective. Due to a common sense deconstruction of human rights and its following reconstruction, normatizing documents of the school curricum are annalysed, the Nacional Curricular Commom Base (BNCC, 2018) and the Curricular Document for Goiás – Ensino Médio part (DC-GOEM, 2020). The field research is characterized by an action-research with the school environment collaboration objective and the recognition of subjects in its following parts as developers of a democractic and rights protective environment. The data collection happened through quizzes, semistructured interviews and teaching and project observation. The reflections were made upon field diary annalysis and student developed production, meaning to understand which is the guiding line that directs the student claimed human rights conception.